Journalists under fire : the psychological hazards of covering war - Feinstein, Anthony (Johns Hopkins University Press, 2006)
Outstanding Academic Title for 2007, Choice Magazine As journalists in Iraq and other hot spots around the world continue to face harrowing dangers and personal threats, neuropsychiatrist Anthony Feinstein offers a timely and important exploration into the psychological damage of those who, armed only with pen, tape recorder, or camera, bear witness to horror. Based on a series of recent studies investigating the emotional impact of war on the profession, Journalists under Fire breaks new ground in the study of trauma-related disorders. Feinstein opens with an overview of the life-threatening hazards war reporters face—abductions, mock executions, the deaths of close colleagues—and discusses their psychological consequences: post-traumatic stress disorder, depression, deterioration of personal relationships, and substance abuse. In recounting the experiences of reporters who encounter trauma on the job, Feinstein observes that few adequate support systems are in place for them. He tells the stories of media veterans who have "seen it all, " only to find themselves and their employers blindsided by psychological aftershocks. The book explores the biological and psychological factors that motivate journalists to take extraordinary risks. Feinstein looks into the psyches of freelancers who wade into war zones with little or no financial backing; he examines the different stresses encountered by women working in a historically male-dominated profession; and he probes the effects of the September 11 attacks on reporters who thought they had sworn off conflict reporting. His interviews with many of this generation's greatest reporters, photographers, and videographers often reveal extraordinary resilience in the face of adversity. Journalists under Fire is a look behind the public persona of war journalists at a time when the profession faces unprecedented risk. Plucking common threads from disparate stories, Feinstein weaves a narrative that is as fascinating to read as it is sobering to contemplate. What emerges are unique insights into lives lived dangerously.